2015
DOI: 10.1097/fpc.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Function-impairing polymorphisms of the hepatic uptake transporter SLCO1B1 modify the therapeutic efficacy of statins in a population-based cohort

Abstract: Background The efficacy of statins, which are used commonly in primary and secondary prevention of cardiovascular diseases, shows a wide range of interindividual variability. Genetic variants of OATP1B1, a hepatic uptake transporter, can modify access of statins to its therapeutic target, thereby potentially altering drug efficacy. We studied the impact of genetic variants of OATP1B1 on the lipid-lowering efficacy of statins in a population-based setting. Materials and methodsThe basis of the analysis was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…ABCC2, carrying the variant rs2002042 that was identified by RF analysis as well, belongs to a family of transporters known to interact with lipophilic statins (23). Interestingly, in our context of elderly individuals, SLCO1B1 SNPs did not show a major role on LDL-C response to statins as shown in previous studies (25). Interestingly, in our context of elderly individuals, SLCO1B1 SNPs did not show a major role on LDL-C response to statins as shown in previous studies (25).…”
Section: Discussionsupporting
confidence: 73%
“…ABCC2, carrying the variant rs2002042 that was identified by RF analysis as well, belongs to a family of transporters known to interact with lipophilic statins (23). Interestingly, in our context of elderly individuals, SLCO1B1 SNPs did not show a major role on LDL-C response to statins as shown in previous studies (25). Interestingly, in our context of elderly individuals, SLCO1B1 SNPs did not show a major role on LDL-C response to statins as shown in previous studies (25).…”
Section: Discussionsupporting
confidence: 73%
“…We estimate that patients with both risk factors are likely to have a much higher chance of developing myopathy. In addition, it is worth noting that both the FDA and the UK Medicines and Healthcare products Regulatory Agency propose a 50% lower dose of simvastatin for patients who coadminister amlodipine -it is unknown how this practice will influence the clinical outcomes of simvastatin treatment, particularly in patients carrying the SLCO1B1 c.521T>C variant, who are less responsive to simvastatin [33,34]. In conclusion, SLCO1B1 geno typing may be critical for simvastatin users who unavoidably take CYP3A4 inhibitors such as amlodipine, in order to lower the risk of adverse effects and impaired drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…OATP1B1 (coded for by SLCO1B1 gene) is involved in the hepatic uptake of many substrates and plays an important role in transporting LPV [11][12][13], thus, genetic variation in SLCO1B1 is likely to affect LPV plasma variability. SLCO1B1 c.521T>C was monomorphic in this African cohort yet its effects on disposition of statins has been extensively reported among Caucasians, African-Americans [28][29][30][31] and Asians [32]. We cannot rule out a role for SLCO1B1 genetic variation in LPV plasma variability, but, can deduce that there could be other African-specific variants that have not yet been reported that need to be investigated.…”
Section: Correlation Between Genetic Variation and Lopinavir Dispositionmentioning
confidence: 63%
“…We did not find significant genetic predictors of LPV plasma concentration. Several studies among Caucasians [18,[26][27][28][29][30] have reported an association of CYP3A4*22 with increased drug plasma concentrations for drugs that are substrates of CYP3A4, however, in this cohort, the allele was absent (0%) yet LPV plasma concentration variability was still huge (>1800-fold). This shows that there could still be some variants in CYP3A4 among African populations that need to be discovered and reported.…”
Section: Correlation Between Genetic Variation and Lopinavir Dispositionmentioning
confidence: 92%